Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/corg.12093
|View full text |Cite
|
Sign up to set email alerts
|

Power and Paradigms: The Dutch Response to Pressures for Shareholder Value

Abstract: Manuscript Type Empirical Research Question/Issue In recent years, research aimed at identifying and relating the antecedents and consequences of diffusing organizational practices/ideas has turned its attention to debating the international adoption and implementation of the Anglo‐American model of corporate governance, i.e., a shareholder value orientation (SVO). While financial economists characterize the adoption of an SVO as necessary and performance‐enhancing, behavioral scientists have disputed such cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 104 publications
(200 reference statements)
2
22
1
Order By: Relevance
“…The most intuitive explanation could be that the strong shareholder protection in one‐tier systems fosters a short‐term focus on financial performance indicators opposed to employee protection (Kwee et al ., ; Moerland, ; Weimer and Pape, ) and, therewith, emphasizes exploitative activities. In turn, two‐tier boards associated with the Rhineland model generally face less shareholder pressure (Bezemer et al ., ). Associated legal and political systems emphasize the rights of other stakeholders (e.g., employees) that are generally more concerned with the long‐term well‐being of the firm rather than short‐term returns.…”
Section: Discussionmentioning
confidence: 97%
“…The most intuitive explanation could be that the strong shareholder protection in one‐tier systems fosters a short‐term focus on financial performance indicators opposed to employee protection (Kwee et al ., ; Moerland, ; Weimer and Pape, ) and, therewith, emphasizes exploitative activities. In turn, two‐tier boards associated with the Rhineland model generally face less shareholder pressure (Bezemer et al ., ). Associated legal and political systems emphasize the rights of other stakeholders (e.g., employees) that are generally more concerned with the long‐term well‐being of the firm rather than short‐term returns.…”
Section: Discussionmentioning
confidence: 97%
“…Amongst different ownership groups, independent institutional investors are more powerful in terms of uniformity of demand as they provide a significant amount of resources and can act independently of the insider's agenda (Almazan, Hartzell, & Starks, 2005). Prior research has demonstrated that independent institutional investors prefer an Anglo-American model as it emphasizes maximization of shareholder value (Bezemer et al, 2015;Chizema, 2008) and they take actions in line with an Anglo-American model to protect their legitimacy in a contested environment (Bates & Hennessy, 2010).…”
Section: Hypothesesmentioning
confidence: 99%
“…Finally, future research should test whether the current findings generalize to non‐U.S. countries with different cultures, socioeconomic institutions, and governance models (Bezemer, Zajac, Naumovska, van den Bosch, & Volberda, ; He & Fang, ). Such research would advance our understanding of the impact of signaling on governance outcomes in various institutional settings.…”
Section: Discussionmentioning
confidence: 94%